Influence of Leadership Style, Work Culture, and Job Satisfaction on Employee Engagement - Pong Bija, Andarias (KnE Social Sciences, 2020)
Employee engagement is important in an organization. In order to realize employee engagement, various experts and literature explain that there is an influence of leadership style, work culture, and job satisfaction. Therefore, this study aims to analyze the influence of leadership style, work culture, and job satisfaction on employee engagement. Taking the object of research at the Ministry of Defense of the Republic of Indonesia, this study uses a quantitative approach in which research data is collected through surveys. Data were analyzed descriptively and inferentially. The results showed that leadership style, work culture, and job satisfaction had a significant influence on employee engagement at the Ministry of Defense of the Republic of Indonesia. All path coefficients are significant at α = 0.05, because all values are greater than t table. Path coefficient value X1 (leadership style) to Y (employee engagement) of py2 = 0.198, and X3 ( job satisfaction) to Y (employee engagement) of py3 = 0.535. Employees at the Ministry of Defense have an enthusiastic, dedicated, and caring attitude. Keywords: leadership style, work culture, job satisfaction, employee engagement